Sistem Infromasi Geografis Pencarian Rute Terpendek Klinik Bersalin Di Kota Tebing Tinggi Menggunakan Algoritma Floyd Warshall Berbasis Android - Rani Antika Lubis; Triase Triase; Aninda Muliani Harahap (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Maternity clinics are often spread across different locations, making it difficult for expectant mothers to find facilities that match their preferences and needs. As a result, many pregnant women who require routine check-ups, pregnancy programs, or delivery services tend to depend on recommendations from relatives without having adequate knowledge about the clinic’s quality, which can lead to dissatisfaction. To overcome this problem, this study develops a geographic information system that incorporates the Floyd–Warshall algorithm to determine the shortest route to each maternity clinic and integrates Mapbox to visualize clinic locations interactively. The research applies quantitative data collection methods and adopts the waterfall system development model to ensure a structured and systematic process. The system aims to offer practical, accurate, and easily accessible information regarding clinic locations, facilities, and routes, thereby helping pregnant women make more informed decisions when selecting maternity services that best suit their needs.